Assessment of Weed Competition Critical Period in Sugar Beet - Doğan Işık; Adem Akça (Journal of Agricultural Sciences, 2018)
Weed control constitutes the most essential issue in cropping systems. The critical periods should especially be determined for each crop. Field experiments were conducted during the seasonal growing periods of sugar beet in 2012 and 2013 in Kayseri, Turkey to assess the critical weed control period (CPWC). A log-logistic model having four parameters was used to assist in monitoring and analyzing two sets of related, relative crop yield. Data was obtained during the periods of increased weed interference and as to compare, during the weed-free periods. In both years, the relative root yield of sugar beet decreased with a longer period of weed-interference and increased where there was a longer weed-free period. In 2012, the CPWC varied between 122-595 GDD (growing degree days) corresponding to 12 to 46 days after crop emergence (DAE). The following year, CPWC were found to be between 82-735 GDD, (8-54 DAE) based on 5% acceptable yield loss. Weed-free conditions are needed to be arranged as early as the first week after crop emergence and maintained up to and including nine weeks thereafter to avoid more than a 5% loss in sugar beet root yield. Those results could assist sugar beet producers through reducing the expenses significantly, as well as improving the efficacy of their weed management programs.